Invisible Agents of Rural Development. Russian Immigrant Women in the Finnish Border Region - Sireni, Maarit; Pöllänen, Pirjo; Davydova-Minguet, Olga (Frontiers in Sociology, 2021)
The rural region of North Karelia is located close to the Finnish-Russian border, and faces challenges due to population decline and labor shortage. However, it has a unique strength which is its proximity to Russia. This paper analyses the perceived role of immigration in enhancing the vitality of North Karelia. It investigates how the impact of immigration is presented in the regional media, and how Russian-speaking immigrant women themselves describe their roles as agents of development. The analysis is based on text material obtained from the regional newspaper, and ethnographic interviews conducted among Russian-speaking immigrant women. Findings based on the newspaper material indicate that immigrants are valued primarily for their contribution to regional economic development. However, in some of the texts, immigrants are presented as an integral part of the region’s population, who diversify the skills of communities and thus create potential for promoting local resilience. The analysis of the ethnographic data indicates that the proximity of the border, trans-local connections, and ethno-cultural capital which is based on immigrants’ national background are important factors that impact on the attractiveness of North Karelia for Russian immigrant women. Everyday trans-local multiculturalism embraces women’s precarious employment which impacts on the well-being of broader communities on both sides of the border. Although Russian immigrant women are a vital part of these communities, they do not themselves participate in the newspaper discussions about the vitality of rural communities. This indicates that Russian women are “invisible” agents of rural development, who are not fully recognized as contributors of resilience in North Karelia.